Grebek Sehat Sebagai Upaya Deteksi Dini Penyakit Tidak Menular Masyarakat Dusun Batur - Dana Daniati; Gunarmi; Sunartono; Karlina; Retno Hastri; Ihwana Musatry Dewi; I Gusti Ayu Raras Pramininingrum; Herlina Juniati M. (J.Abdimas: Community Health, 2020)
Non-communicable disease is a health threat to all age groups in society. High mobility and activity make people not pay attention to health and do not apply germas such as doing physical activity, eating fruits and vegetables, and conducting regular health checks to detect risk factors that exist in each person. Grebek Sehat is an effort to control non-communicable diseases, can improve the knowledge and skills of officers and cadres, especially in carrying out early detection activities, monitoring and following up on risk factors for non-communicable diseases optimally so that it is hoped that it can help in reducing the rate of increase in non-communicable diseases in the community.